PENGARUH PENERAPAN MODEL GENERATIVE LEARNING TERHADAP PENCAPAIAN KOMPETENSI IPA SISWA KELAS VIII SMPN 7 PADANG - Monica Fitri Yani; Yurnetti Yurnetti; Gusnedi Gusnedi (Universitas Negeri Padang, 2016)
The problem in this research is the extent to effect of applying the generative learning model towards achivement of competence IPA student of class VIII SMPN 7 Padang. Generative learning model is designed so that students can improve conceptual understanding and critical thinking of students through interactive participation in learning activities and can increase students' motivation by involving students directly in the discovery of a concept. This research was a quasi-experimental with pretest-Posttest control group design, the two groups selected at random, and then given a pretest to determine the initial state between the experimental group and the control group. The population in this study were all students of class VIII SMPN 7 Padang enrolled in academic year 2015-2016, the sample was taken using cluster random sampling technique. Competence knowledge is measured using written tests, competency attitudes measured using observation sheet and skill competencies are measured using performance assessment rubric. Data competence of knowledge, competence, attitudes and skills competency test were analyzed using two average similarity with the real level of 0.05. Based on research data, obtained an average student learning outcomes in the experimental class competencies of knowledge, attitudes and skills higher than the control class. The results of data analysis using a third competency test the equality of two average with the real level of 0.05 indicates that th> tt, this means that there is a significant impact on the application of the model Generative Learning competency achievement grade science students SMPN 7 Padang